HUBUNGAN DUKUNGAN KELUARGA DENGAN PERUBAHAN KONSEP DIRI PADA PASIEN PASCA STROKE DI POLIKLINIK SYARAF RUMAH SAKIT STROKE NASIONAL BUKITTINGGI TAHUN 2016 - Melti Suriya (JIK-JURNAL ILMU KESEHATAN, 2018)
ABSTRACTWorld Health Organization (WHO) in 2014 shows that 63% of death case world widely wass caused by non-communicable diseases, namely stroke or it is equivalent to 36 million deaths a year. Post-stroke patient who see themselves negatively not able to see the positive side of the defect in misery. The patient sees himself as an individual with a disability, unable to meet the demands of the moral, full of flawar. The purpose of this study is to determine the relationship between family support and self-concept changes in post-stroke patients in National Stroke Hospital of Bukittinggi 2016. The type of analytical research was cross sectional design. The population of this research was the total number of stroke haemoragic who visited in February - March 2016 there were 366 people with 46 of the sampling. The sampling technique Accidental sampling. This research was held on June 06- 17 june 2016. These Data were analyzed by using univariate which used frequency distribution table and bivariate which use statistical test Chi-Square with α 95% confidence level α = 0.05. The results of the research showed that less than (43.5%) respondents have negative self-concept. More  than (41.3%) respondents have unsupported family. There was a relationship between family support and self-concept (p value = 0,010). In conclusion family support can affect self-concept in stroke patients. Health worker aslo can be expect in National Stroke Hospital of Bukittinggi can give the information to post stroke patients family to regard the post stroke patien and can give counseling guidance about the importance of family support for build the self-concept of post-stroke patient to make then feel more confident with their condition. Keywords: Stroke, Family Support and Self-Concept                                                             ABSTRAKMenurut World Health Organization (WHO) tahun 2014 menunjukkan bahwa 63% penyebab kematian di seluruh dunia disebabkan oleh penyakit tidak menular yaitu stroke atau setara dengan kematian 36 juta jiwa per tahun. Pasien pasca strok yang memandang dirinya secara negatif tidak mampu memandang sisi positif dari cacat yang dideritanya. Pasien tersebut memandang dirinya sebagai indivindu yang cacat, tidak mampu memenuhi tuntutan moral, penuh kekurangan. Tujuan penelitian ini untuk mengetahui hubungan dukungan keluarga dengan perubahan konsep diri pada pasien pasca stroke di Poliklinik Syaraf Rumah Sakit Stroke Nasional Bukittinggi tahun 2016.Jenis penelitian analitik dengan desain cross sectional. Populasi dalam penelitian ini adalah seluruh pasien stroke haemoragik yang datang berkunjung di Poliklinik Syaraf Rumah Sakit Stroke Nasional Bukittinggi pada bulan Februari – Maret 2016 sebanyak 366 orang dengan sampel 46 orang. Teknik pengambilan sampel accidental sampling. Penelitian dilakukan pada tanggal 06 – 17 Juni 2016. Data dianalisa secara univariat menggunakan table distribusi frekuensi dan bivariat menggunakan ujia statistik Chi-Square dengan tingkat kepercayaan 95% α = 0,05.Hasil penelitian menunjukan bahwa kurang dari separuh 43,5% memiliki konsep diri negatif. Kurang dari separuh 41,3% memiliki keluarga tidak mendukung. Ada hubungan dukungan keluarga dengan konsep diri di Poliklinik Syaraf Rumah Sakit Stroke Nasional Bukittinggi tahun 2016 (p value = 0,010).Kesimpulan penelitian ini adalah ada hubungan dukungan keluarga dengan konsep diri pasien stroke. Diharapkan tenaga ksehatan di Poliklinik Syaraf Rumah Sakit Stroke Nasional Bukittinggi agar dapat memberikan informasi kepada pasien pasca stroke agar dapat memberikan bimbingan konseling tentang pentingnya dukungan keluarga terhadap konsep diri pada pasien pasca stroke sehingga pasien dapat percaya diri dengan keadaanya sekarang.